Strategic Evaluation in Development Teacher Competency - Gufron, Moh; Ningsih, Putri Rahayu; Winarto, Winarto (Technium Education and Humanities, 2024)
A quality school will have various programs that are of interest to educational users. A quality school will also be supported by quality human resources as well as professionalism. Teaching is classified as a professional job, because it requires special abilities (techniques). With these special techniques and skills that must be possessed, a teacher plays a significant role and has a very strategic position in determining the success or failure of learning activities. So that this learning process will determine the quality of education in the educational unit. This research seeks to analyze and find strategic evaluations of teacher competency development. This research uses a qualitative approach, phenomenological type with a multisite design. Data collection techniques using in-depth interviews, participant observation and documentation. Data analysis uses the Myles Huberman model of data reduction, data presentation, verification and drawing conclusions. Test the validity of the data through credibility, transferability, dependability and confirmability.The results of the research show: strategic evaluation of teacher competency development is carried out in the teacher performance assessment system, position promotion is based on a reward and punishment system.